2021
DOI: 10.1111/psyg.12655
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of factors associated with persistent delirium

Abstract: Background It has been reported that delirium causes various problems. Many researchers have reported the risk factors associated with the onset of delirium; however, there are few reports focused on persistent delirium. This study aimed to identify the risk factors associated with persistent delirium. Methods A total of 573 patients hospitalised in Nara Prefecture General Medical Centre from October 2014 through September 2017 who were referred to the psychiatry consultation service were included in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…For study purposes the definition of persistent delirium differed. Goto et al., 2021 ; Kenes et al., 2017 ; Leonard et al., 2014 ; Meagher et al., 2012a ; Mistraletti et al., 2012 ; Morandi et al., 2012 . Course of time Duration could be categorized as: Rapid Recovers: severe delirium and symptoms quickly resolved within 60 h; Slow Recovers: gradually declined over the 7-day period; Non recovers: persisted over the 7-day assessment period Lindroth et al., 2020 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For study purposes the definition of persistent delirium differed. Goto et al., 2021 ; Kenes et al., 2017 ; Leonard et al., 2014 ; Meagher et al., 2012a ; Mistraletti et al., 2012 ; Morandi et al., 2012 . Course of time Duration could be categorized as: Rapid Recovers: severe delirium and symptoms quickly resolved within 60 h; Slow Recovers: gradually declined over the 7-day period; Non recovers: persisted over the 7-day assessment period Lindroth et al., 2020 .…”
Section: Methodsmentioning
confidence: 99%
“…For study purposes the definition of persistent delirium differed. Goto et al, 2021;Kenes et al, 2017;Leonard et al, 2014;Meagher et al, 2012a;Mistraletti et al, 2012;Morandi et al, 2012.…”
Section: Persistentmentioning
confidence: 99%
“…Regarding the clinical features of persistent delirium, Meagher et al 7 studied 100 delirium patients with an average age of 70.2 years (range, 36-90) and reported that the factors likely to predict persistent delirium were more severe disturbances of orientation, short-and long-term memory, delusions, motor agitation, inattention, and thought process abnormalities, suggesting that persistent delirium increasingly emphasised recognised core diagnostic features and cognitive dysfunction. Goto et al 8 examined the risk factors associated with persistent delirium in 227 delirium patients with an average age of 76.4 years (range, 32-96) in a retrospective study. Of the 227 patients, 46 (20.3%) had persistent delirium, defined as delirium lasting for 14 days or more.…”
Section: Persistence Of Deliriummentioning
confidence: 99%